Transcriptional regulation of the protein kinase a subunits in Saccharomyces cerevisiae during fermentative growth - Galello, Fiorella Ariadna (2017)
Yeast cells can adapt their growth in response to the nutritional environment. Glucose is the favourite carbon source of Saccharomyces cerevisiae, which prefers a fermentative metabolism despite the presence of oxygen. When glucose is consumed, the cell switches to the aerobic metabolism of ethanol, during the so-called diauxic shift. The difference between fermentative and aerobic growth is in part mediated by a regulatory mechanism called glucose repression. During glucose derepression a profound gene transcriptional reprogramming occurs and genes involved in the utilization of alternative carbon sources are expressed. Protein kinase A (PKA) controls different physiological responses following the increment of cAMP as a consequence of a particular stimulus. cAMP–PKA is one of the major pathways involved in the transduction of glucose signalling. In this work the regulation of the promoters of the PKA subunits during respiratory and fermentative metabolism are studied. It is demonstrated that all these promoters are upregulated in the presence of glycerol as carbon source through the Snf1/Cat8 pathway. However, in the presence of glucose as carbon source, the regulation of each PKA promoter subunits is different and only TPK1 is repressed by the complex Hxk2/Mig1 in the presence of active Snf1.